Changes in Psychopathology and Mental Health Resilience - Onchev, Georgi (Frontiers in Psychiatry, 2021)
Accelerated culture transition and contemporary post-truth mass cognitive distortions contribute to cognitive insecurity and substitution of facts with opinions. In this paper the impact of these changes on normal psyche and on psychopathological manifestations and mental health care is described. The consequences include drop of mental resilience, pathomorphosis of some clinical pictures, blurring of diagnostic boundaries, mimicry of psychopathology, and overdiagnosis. Their repercussions on mental health care and professional integrity are discussed, and particularly the need for shift of mental health care focus from protection to resilience is disputed.